Dynamic Forces of Swaying Human and Responses of Temporary Demountable Grandstand Based on Experiment and Simulation - Lin He; Jian Yuan; Feng Fan; Cong Liu (Shock and Vibration)
Modern temporary demountable structures must be designed to withstand the dynamic forces which generated by crowd occupants. The human forces and that cause the dynamic responses of structure have become an important research topic. In this paper, the human swaying forces and responses of temporary demountable grandstand are studied through an experimental program. The dynamic forces that were induced by participants who have swayed 0.5–1.8 Hz are recorded by a triaxial human biomechanics force plate, and the structural dynamic responses of a temporary grandstand occupied twenty swaying human are investigated. The constraint parameters of swaying force model which derives from a semiempirical formula are developed and can be represented for crowd. Crowd can able to induce excessive lateral vibration of structure due to the lower frequency of temporary grandstand and make them in panic. The dynamic responses of a large temporary grandstand are predicted by finite element method, and the results show that a person was considered as a load with stiffness and damping, and the structural lateral dynamic responses are higher than the model of person just only considered as load.